Decreased beta 2-adrenoceptor density and decreased isoproterenol induced c-AMP increase in juvenile type I diabetes mellitus: an additional cause of severe hypoglycaemia in childhood diabetes? - Schwab, K O; Bartels, H; Martin, C; Leichtenschlag, E M (European journal of pediatrics, 1993)
Little is known about the receptor and post receptor mechanisms of sympathoadrenal signal transmission in type I diabetes mellitus. Therefore, we examined the maximum binding of granulocyte beta 2-adrenoceptors and the in vitro c-AMP accumulation in lymphocytes of 24 children and adolescents with diabetes mellitus and 14 similarly aged healthy subjects. The number of high affinity beta 2-adrenoceptors on granulocytes correlated significantly with unstimulated (r = 0.6, P < 0.004) and with isoproterenol stimulated c-AMP values in lymphocytes (r = 0.68, P < 0.0007) showing the proportional changes of beta 2-adrenoceptors and c-AMP in two different cells. The number of beta 2-adrenoceptors on granulocytes was significantly reduced in diabetic as compared to healthy children (median 1397, range 599-3405 vs. 2205, 825-3200 beta 2-adrenoceptors per granulocyte, P = 0.014). Moreover, the percentage in vitro stimulation of c-AMP by isoproterenol in lymphocytes was significantly reduced in diabetic children as compared to healthy individuals (120%, 39%-278% vs. 225%, 66%-500%, P = 0.012). These results indicate a decreased sympathoadrenergic signal transmission in peripheral blood cells as a model for the liver probably contributing to severe hypoglycaemia in diabetic children.